Effect of soil water availability on gas exchange in young trees of Eucalyptus grandis W. Hill ex Maiden - María Sara Mejía de Tafur; Néstor Miguel Riaño Herrera; John Byron Urrego Mesa; Dora Mónica Ibarra Espinosa; Claudia Marcela Zapata Duque (Acta Agronómica)
Two outdoor trials were conducted in the department of Valle del Cauca, Colombia, in contrasting climatic conditions, to evaluate the effect of soil water availability on the gas exchange of four elite genotypes of Eucalyptus grandis as follows: 28-3, 18-3, 24A-5 and 19-1, respectively. One trial was conducted on the campus of the Universidad Nacional de Colombia located in Palmira, at 994 m.a.s.l. with an average temperature of 23.5°C (maximum of 31°C, minimum of 18°C), and 76% relative humidity (RH). The second trial was conducted at the nursery of Carton de Colombia S.A., located in Restrepo, at 1450 m.a.s.l. with an average temperature 18°C (maximum of 26°C, minimum of 12°C) and 80% RH. A split-plot design with four replicates was used. Treatments were field capacity (FC), ½ FC, ¼ FC, and soil waterlogging. At both locations, pot surfaces were covered with plastic sheeting to prevent the entrance of rainfall. Significant differences between water regimes, genotypes and locations occurred in photosynthesis rate, internal CO2 of the substomatal cavity (Ci), stomatal conductance, and transpiration rate, indicating that E. grandis has physiological defense mechanisms to drought stress such as stomata closure, evidenced by a decreasing in photosynthesis rate, stomatal conductance, and transpiration rate. A differential response was also observed between genotypes depending on the environment, indicating a genotype x environment interaction in terms of plant physiological response. Eucalyptus grandis appears to save water under water stress conditions by a decreasing in photosynthesis rate. Excess water is more limiting than water deficit.